2011
DOI: 10.1068/ic338
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Viscosity of PDMS Based Silicone-Oil Tamponade Agents on the Movement Relative to the Eye Wall during Eye Movements

Abstract: Silicone oil tamponade is used as vitreous substitute to treat complicated retinal diseases. It provides support to the retina and acts against contraction of the retina and as such plays a vital role in preventing eyes from certain blindness. Silicone oil however has a tendency to emulsify and is accountable to inflammation and glaucoma. In in-vitro study, it was found that using silicone-oil with higher viscosity reduce the occurrences of emulsifications. In this study, an eye model chamber was used to captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several in vitro studies demonstrated that higher viscosity silicone oils tend to emulsify less [ 9 11 ]. These findings led to several investigations of high viscosity silicone oils [ 14 18 ]. However, the silicone oils used in these studies were obtained by adding low concentrations (5–10%) of long chain silicone molecules to regular silicone oil, and not by using uniformly high viscosity oils, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies demonstrated that higher viscosity silicone oils tend to emulsify less [ 9 11 ]. These findings led to several investigations of high viscosity silicone oils [ 14 18 ]. However, the silicone oils used in these studies were obtained by adding low concentrations (5–10%) of long chain silicone molecules to regular silicone oil, and not by using uniformly high viscosity oils, as in the current study.…”
Section: Discussionmentioning
confidence: 99%